Características dos sistemas de controle gerencial de empresas de prestação de serviços em tecnologia da informação: um estudo de casos múltiplos - Magalhães, Marcelo Nassif de (2016)
This survey studied the characteristics of management control systems of six companies providing services in Information Technology, and three from Brazil and three foreigners, who have an office in the state of Rio de Janeiro and are internationalized. Methodology used was the study of case with the results of content analysis. Following conditions are met: 1) the origin of Brazilian companies seem to adopt the framework of Lorange and Morton, while those of foreign origin companies seem to adopt the reference framework of Flamholtz; 2) the origin of Brazilian companies have the organizational control of kind "by results" and of foreign origin companies, have the organizational control of the "bureaucratic"; 3) four of the companies surveyed use cost center as kind of responsibility center; 4) preferred strategy is the cost leadership; 5) companies use budget, ROI, BSC, ABC costing, corporate governance criteria and customer satisfaction measures such as management control tools; 6) companies using management information systems, ERP, CRM, PMBOK, and IT governance as technological tools to support the Management Control; 7) the political and economic crisis facing the country is directly affecting the control of companies, which are having to adjust their controls to minimize the economic and financial impact on the results, and; 8) four companies studied are in stage IV of internationalization, according to Uppsala. These companies, three are multinationals, two global and one exporter. What had motivated internationalization, in three of these companies, it was the search for market opportunities in two, the search for market diversification, and one, the search for economies of scale.